2000
DOI: 10.1901/jaba.2000.33-13
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Effects of Matched Stimuli on Behaviors Maintained by Automatic Reinforcement

Abstract: The purpose of the current investigation was to extend the literature on matched stimuli to three dissimilar forms of aberrant behavior (dangerous climbing and jumping, saliva manipulation, and hand mouthing). The results of functional analyses suggested that each behavior was automatically reinforced. Preference assessments were used to identify two classes of stimuli: items that matched the hypothesized sensory consequences of aberrant behavior (matched stimuli) and items that produced sensory consequences t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
205
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(216 citation statements)
references
References 15 publications
8
205
1
2
Order By: Relevance
“…Although the particular sensory function being stimulated may not always be visually apparent to an observer, stereotypies often provide an obvious source of sensory input (e.g., visual, auditory, tactile vestibular, taste, or smell). Additionally, single-subject research has shown that interventions that either remove the sensory component of stereotypy (e.g., sensory extinction), or provide alternative but age-appropriate forms of sensory input (e.g., functional matching procedures), lead to a reduction in stereotypic behaviors for many children (Piazza, et al, 2000;Rapp, 2006;Rapp, 2007;Rincover, 1978;Rincover, et al, 1979). Lastly, several studies have demonstrated that allowing children with autism to engage in stereotypic behaviors contingent upon other target behaviors is reinforcing and without negative side effects (Charlop, Kurtz, & Casey, 1990;Hanley, Iwata, Thompson, & Lindberg, 2000;Kennedy, et al, 2000;Wolery, Kirk, & Gast, 1985).…”
Section: Stereotypy As Self-stimulatory Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…Although the particular sensory function being stimulated may not always be visually apparent to an observer, stereotypies often provide an obvious source of sensory input (e.g., visual, auditory, tactile vestibular, taste, or smell). Additionally, single-subject research has shown that interventions that either remove the sensory component of stereotypy (e.g., sensory extinction), or provide alternative but age-appropriate forms of sensory input (e.g., functional matching procedures), lead to a reduction in stereotypic behaviors for many children (Piazza, et al, 2000;Rapp, 2006;Rapp, 2007;Rincover, 1978;Rincover, et al, 1979). Lastly, several studies have demonstrated that allowing children with autism to engage in stereotypic behaviors contingent upon other target behaviors is reinforcing and without negative side effects (Charlop, Kurtz, & Casey, 1990;Hanley, Iwata, Thompson, & Lindberg, 2000;Kennedy, et al, 2000;Wolery, Kirk, & Gast, 1985).…”
Section: Stereotypy As Self-stimulatory Behaviormentioning
confidence: 99%
“…Researchers suggest that noncontingent access to stimuli matched in sensory function to the preferred sensory reinforcer may reduce the establishing operation (EO) for stereotypy and its frequency of occurrence (Piazza, et al, 2000;Rapp, 2006). For example, a child who engages in repetitive spinning of objects for the visual sensory feedback might be provided with noncontingent access to spin tops.…”
Section: Stereotypy As Self-stimulatory Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research supports the use of noncontingent reinforcement via reinforcement of preferred object manipulation to decrease other topographies of automatically maintained challenging behavior (Britton et al 2002;Lindberg et al 2003). Antecedent manipulations, specifically environmental enrichment, have demonstrated success in the reduction of automatically maintained problem behavior as well (Piazza et al 2000;Rapp and Vollmer, 2005;Vollmer et al 1994). The availability of preferred stimuli may indirectly compete with the reinforcement provided by automatically maintained ISB, thereby reducing the frequency of ISB.…”
Section: A Clinical Model For Treatmentmentioning
confidence: 90%